Analysis of The Influence of Digital Financial Literacy Understanding on The Profitability of Small and Medium Micro Enterprises - Parandy, La Mema; Ratna Tungga Dewa, Dominica Maria; Adhi Pramono, Susatyo; Restu Suwondo, Juwita Purnami; Nurdiani, Tanti Widia (SEULANGA SYSTEM PUBLISHER, 2024)
The objective of this study is to impact the financial knowledge of micro, small, and medium firms in order to improve their profitability. This study utilizes primary data obtained through interviews and questionnaires delivered to participants. This study is based on causal research. The research focuses on Micro, Small, and Medium Enterprises (MSMEs). This study employs non-probability sampling methods. Purposive sampling is the approach utilized. The study used the multivariate structural equation model approach. The research results indicate a notable correlation between financial attitude, financial conduct, financial knowledge, and profitability. Financial attitude significantly influences profitability, with higher levels of financial attitude leading to increased profitability. Furthermore, improved financial behavior positively impacts profitability, indicating that those with better financial habits can attain higher levels of profitability. Financial knowledge significantly impacts profitability, with better financial understanding leading to increased profitability. Thus, improving financial attitude, financial behavior and financial knowledge can increase individual or company profitability.